Los programas televisivos y las manifestaciones emocionales de los niños y niñas de 4 a 8 años de edad - García Tejedo, Sonia (2008)
Since the conception of man as a biological and social being the idea that the human being is a being of needs that have to meet them for development in fulfilling their life cycle follows. In this sense the idea that human • being coined from birth begins its process of socialization. In this stage of childhood where lays the foundation for the profile of adult life, the child requires support and proper guidance to affirm the foundations of his personality, in order to achieve their full development as a person, but not so when the intervention of other socializing agents that hinder some learning as social skills is neglected. We conceive childhood as a unique and important stage in the life of a person who provides the necessary foundation for adult life Santrock (2004, p 42). The basics needed for adult life, the child is acquiring him in his environment through education can be formal and informal. It is known that the first takes place in an educational institution and is intentional and organized; that is developed according to policy guidelines. The Ministry of Education-(2005) states that "education contributes to the development and integral education of children", one of the issues to address in the development and comprehensive training is the social growth; that is, keep in mind that children need to learn social skills. Meanwhile informal education is unsystematic, unorganized, not intentionally, but largely influences the educational process of the person. Today the natural environment where informal education, which relates to human beings and their environment is being controlled television develops. Children learn social skills in the process of interaction with the context, family, school and television. With respect to the latter it is considered an interactive agent because children are in front of her most of the time. In addition, television is the instrument of distraction and fun for children's entertainment broadcasts programs, which dominate cartoons, laden with violence and affect the emotions of children. Therefore, one of the most destructive consequences of violence is the negative effect it has on the emotions of the infant. Children have limited their physical and social world knowledge, as well as manifestations of information processing, therefore reflexively difficult for them to translate messages that transmit television programs; as a result, children internalize positive and negative emotions after watching television programs. Currently there are emotional problems and demand to be treated with a primary component that is emotional stability. But when we lack emotional stability problems are exacerbated, as sL1cede today. That what we must reflect and look what happened to the childhood stage of the current adult generation; also what will happen to the current children about 20 years later. If they are those who spend most of their time in front of television programs such as cartoons full of violence, then they will have positive or negative emotions depending on the program you see